Degradation of Indomethacin in Wastewater: Removal with Sodium Hypochlorite and Analysis of Degradation Byproducts - Antonio Medici; Giovanni Luongo; Lucio Previtera; Daniele Naviglio; Giovanni Di Fabio; Armando Zarrelli (Molecules)
Over the years, the frequent and continuous use of drugs has led to a high presence of emerging micropollutants in wastewater, increasing environmental and health concerns. Among these chemicals, Indomethacin (IND), a widely used anti-inflammatory drug, has been detected up to 150 ng/L in water bodies. Its presence in aquatic environments causes increasing concerns due to its high persistence, limited biodegradability, and resistance to conventional treatment processes. This study examined the degradation of IND via oxidation with sodium hypochlorite (NaClO) and the characterization of the degradation byproducts (DPs) generated by this process. Based on NMR spectroscopy studies and mass spectrometry analysis, thirteen DPs were identified, seven of which were previously unpublished (DP1: 2-(3-Chloro-1-(4-chlorobenzoyl)-2-hydroxy-5-methoxy-2-methylindolin-3-yl)acetic acid, DP3: 2-(3,4-Dichloro-1-(4-chlorobenzoyl)-2-hydroxy-5-methoxy-2-methylindolin-3-yl)acetic acid, DP5: (3-Chloro-5-methoxy-2-methyl-1H-indol-1-yl)(4-chlorophenyl)methanone, DP6: (4-Chlorophenyl)(5-methoxy-3-(methoxymethyl)-2-methyl-1H-indol-1-yl)methanone, DP7: 2-(2-(4-Chlorobenzamido)-5-methoxyphenyl)-2- oxoethyl acetate, DP8: 2-(5-Methoxy-2-methyl-1H-indol-3-yl)acetic acid, DP9: 4-Chloro-N-(4-methoxyphenyl)benzamide), and a degradation mechanism was proposed. These results show how the degradation of Indomethacin leads to the generation of new byproducts that may persist in the environment, obtaining DP1 in far larger quantities than the other byproducts. Given Indomethacin’s degradation rate of over 90% but not its complete mineralization, it is fundamental to study not only IND but also the byproducts generated to assess their potential environmental impact.